2020
DOI: 10.1038/s41392-020-00340-2
|View full text |Cite|
|
Sign up to set email alerts
|

Advances in targeted therapy mainly based on signal pathways for nasopharyngeal carcinoma

Abstract: Nasopharyngeal carcinoma (NPC) is a malignant epithelial carcinoma of the head and neck region which mainly distributes in southern China and Southeast Asia and has a crucial association with the Epstein–Barr virus. Based on epidemiological data, both incidence and mortality of NPC have significantly declined in recent decades grounded on the improvement of living standard and medical level in an endemic region, in particular, with the clinical use of individualized chemotherapy and intensity-modulated radioth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 300 publications
(358 reference statements)
0
47
0
Order By: Relevance
“…The function of ECM is primarily involved with the activation of focal adhesion-related pathways, including FAK/SRC, PI3K/AKT and RhoA/ROCK signaling. The predominant ECM components in the NPC microenvironment are collagen (especially type I collagen), lumican, and fibronectin, which all have a positive impact on angiogenesis and anti-apoptosis (50,118,119). Other collagens are also synthesized by intratumoral fibroblasts, such as type III and type IV collagens, but they exhibit patient-specific distribution.…”
Section: Targeting Fibroblasts To Manipulate the Tumor-promoting Extracellular Matrixmentioning
confidence: 99%
“…The function of ECM is primarily involved with the activation of focal adhesion-related pathways, including FAK/SRC, PI3K/AKT and RhoA/ROCK signaling. The predominant ECM components in the NPC microenvironment are collagen (especially type I collagen), lumican, and fibronectin, which all have a positive impact on angiogenesis and anti-apoptosis (50,118,119). Other collagens are also synthesized by intratumoral fibroblasts, such as type III and type IV collagens, but they exhibit patient-specific distribution.…”
Section: Targeting Fibroblasts To Manipulate the Tumor-promoting Extracellular Matrixmentioning
confidence: 99%
“…Genomic, transcriptomic, bioinformatic, and omics studies have indicated that aberrant signal transduction pathways including epithelial growth factor (EGF) receptor (EGFR), nuclear factor kappa-B (NF-κB) [11], WNT/β-catenin [12], PI3K/Akt/mTOR, p53, PARP, MAPK, STAT, cell cycle pathways, and miRNAs/lncRNAs [13,14] may result in tumor progression and treatment resistance in NPC. EGFR is a tyrosine kinase receptor.…”
Section: Introductionmentioning
confidence: 99%
“…Although radiotherapy remains the most essential treatment for NPC, the recurrence rate of the disease is as high as 82% due to radiotherapy resistance 3,4 . In recent years, there has been abundant research on radioresistance, drug resistance, and angiogenesis to uncover the underlying mechanisms for miRNA involvement in NPC progression 5 . Changes in radiotherapy sensitivity and the prognosis of NPC patients can also occur due to changes in miRNA expression.…”
Section: Introductionmentioning
confidence: 99%
“…By in uencing signal pathways, MiRNAs can participate in radiotherapy resistance in NPC cells. For example, NPC cell proliferation and tumor progression are regulated by miR-375, which is up-regulated through the promotion of the pyruvate dehydrogenase kinase 1 (PDK1) / phosphatidylinositol (3,4,5)-trisphosphate (PIP3) / protein kinase B (Akt) axis 6 . In contrast, the down-regulation of miR-429 functions as a tumor suppressor 7 .…”
Section: Introductionmentioning
confidence: 99%